The phenomenon of value-sensory realm of personalities and its place in the axiological discourse of contemporary education - Demianuk, Victor (Journal of Education, Health and Sport, 2016)
The work was defined philosophy and methodological content phenomenon value-sensual sphere. Disclosed and examined the content of the component indicated. Specify the place and importance of the heuristic value phenomenon-sensual sphere of personalities in the axiological discourse of modern education. Defends opinion that education fully the specific role in the formation and development of value-sensual sphere (to the valuable guidance and personal instantiation of the senses). Education is an effective process of socialization, the nature and content filling that has meaning within all life.